2014
DOI: 10.1364/ao.53.008197
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of visible moiré between repetitive periodic-like gratings in the image domain

Abstract: An image domain approach to the interpretation of visible moiré phenomena in repetitive grating multiplicative superposition has been proposed. The local frequency method provides the instantaneous period and orientation of generated moiré. These parameters of the moiré have been sorted into real and pseudo patterns by the Fourier expansions analysis. With the combination of these two steps, the concept "equivalent period contribution threshold" has been introduced. It is found that different thresholds bring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The moiré technique has also been applied to the structural illumination microscopy [6,7]. Yu et al [8,9] worked on the visible moiré patterns and the influence of different grating frequencies on the resulting moiré patterns. Joydeep [10] has shown a method for experimental variation of shape of the moiré patterns generated using interferometry and a Spatial Light Modulator.…”
Section: Literature Surveymentioning
confidence: 99%
“…The moiré technique has also been applied to the structural illumination microscopy [6,7]. Yu et al [8,9] worked on the visible moiré patterns and the influence of different grating frequencies on the resulting moiré patterns. Joydeep [10] has shown a method for experimental variation of shape of the moiré patterns generated using interferometry and a Spatial Light Modulator.…”
Section: Literature Surveymentioning
confidence: 99%
“…Blau et al [5] and Röhrich et al [6] used moiré in structural illumination microscopy. Yu et al [7,8] has performed an in-depth image domain study of the visible moiré patterns. Yu et al [8] has also showed generation of different moiré patterns for different period ratios of the gratings used to produce the moiré patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [7,8] has performed an in-depth image domain study of the visible moiré patterns. Yu et al [8] has also showed generation of different moiré patterns for different period ratios of the gratings used to produce the moiré patterns. Different fringes are generated with different schemes of optical interferometry also.…”
Section: Introductionmentioning
confidence: 99%